Regio- and sequence-controlled conjugated topological oligomers and polymers via boronate-tag assisted solution-phase strategy - Chaoran Xu (Nature Portfolio, 2021)
The topology of polymers could be carefully controlled if the monomers were to be well-defined in sequence and regiochemical linkage. Here the authors present a method to synthesize oligomers of controlled sequence and regiochemistry, formed through iterative liquid-phase boronate-tagged syntheses, which are precursors to topologically distinct polymers.